Pharmacoeconomic study of active psoriatic arthritis treatment - A. V. Rudakova; Т. V. Korotaeva (Фармакоэкономика)
Objective: to conduct a clinical and economic analysis of the therapy for adult patients with psoriatic arthritis (PsA) using netakimab, a Russian interleukin-17 inhibitor, in comparison with other biological (b) and targeted synthetic (ts) disease-modifying antirheumatic drugs (DMARDs), available on the pharmaceutical market of the Russian Federation.Material and methods. The evaluation of clinical and economic effectiveness was carried out from the perspective of the healthcare system for a population of patients with active PsA, based on the results of a network meta-analysis. Clinical effectiveness was analyzed through the changes in articular symptoms according to the American College of Rheumatology ACR70 criteria, as well as changes in cutaneous symptoms evaluated by the Psoriasis Area and Severity Index PASI90. A time horizon of the study was set at 2 years. The costs of pharmaceuticals were calculated based on the registered maximum retail prices, inclusive of value-added tax. In case of availability of biosimilars/generics on the market, calculations were based on the minimum values of the registered prices. The impact of price changes on the study results was assessed using sensitivity analysis.Results. According to the network meta-analysis, the efficacy of netakimab at week 24 significantly surpasses that of adalimumab, apremilast, guselkumab, ixekizumab, secukinumab, tofacitinib, ustekinumab, certolizumab pegol, and etanercept in terms of achieving ACR70; netakimab demonstrated a trend towards higher efficacy in comparison with golimumab and infliximab. The netakimab's efficacy appeared significantly greater than that of adalimumab, golimumab, infliximab, secukinumab, ustekinumab, certolizumab pegol, and etanercept with respect to PASI90 criterion; netakimab exhibited a trend towards higher efficacy in comparison with guselkumab and ixekizumab. The observed clinical effect was accompanied by a significant reduction in healthcare system costs: therapy using comparators over a 2-year study horizon was found to be 6–226% costlier than netakimab-based therapy. The expenditure required to achieve a response based on efficacy criteria was minimal among all evaluated regimens when using netakimab. For comparators, the costs to achieve an additional case of response according to the ACR70 criterion were higher by 127.7–894.6%, and by 59.2–2091.3% according to the PASI90 criterion.Conclusion. The treatment regimen for PsA with netakimab is characterized by the lowest cost compared to other bDMARDs and tsDMARDs, while providing better or comparable clinical effect, thereby indicating a higher clinical and economic effectiveness. In order to ensure costs comparable to those associated with netakimab and responses based on ACR70 and PASI90 criteria, substantial reductions in prices of comparators or provision of additional free packages by the manufacturer are required. The inclusion of netakimab in the treatment regimens for PsA significantly enhances an accessibility of therapy and contributes to an improved prognosis for disease course.